Comparative ab initio calculations of reo3, srzro3, bazro3, pbzro3 and cazro3 (001) surfaces - Eglitis, Roberts; Purans, Juris; Gabrusenoks, Jevgenijs; Popov, Anatoli I.; Jia, Ran (MDPI AG, 2020)
We performed, for first time, ab initio calculations for the ReO2-terminated ReO3 (001) surface and analyzed systematic trends in the ReO3, SrZrO3, BaZrO3, PbZrO3 and CaZrO3 (001) surfaces using first-principles calculations. According to the ab initio calculation results, all ReO3, SrZrO3, BaZrO3, PbZrO3 and CaZrO3 (001) surface upper-layer atoms relax inwards towards the crystal bulk, all second-layer atoms relax upwards and all third-layer atoms, again, relax inwards. The ReO2-terminated ReO3 and ZrO2-terminated SrZrO3, BaZrO3, PbZrO3 and CaZrO3 (001) surface band gaps at the Γ–Γ point are always reduced in comparison to their bulk band gap values. The Zr–O chemical bond populations in the SrZrO3, BaZrO3, PbZrO3 and CaZrO3 perovskite bulk are always smaller than those near the ZrO2-terminated (001) surfaces. In contrast, the Re–O chemical bond population in the ReO3 bulk (0.212e) is larger than that near the ReO2-terminated ReO3 (001) surface (0.170e). Nevertheless, the Re–O chemical bond population between the Re atom located on the ReO2-terminated ReO3 (001) surface upper layer and the O atom located on the ReO2-terminated ReO3 (001) surface second layer (0.262e) is the largest.
We greatly acknowledge the financial support via the ERAF Project No. 1.1.1.1/18/A/073.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; (001) surface; Ab initio methods; ABO3 perovskites; B3LYP; B3PW; ReO3